THE ROLE OF FORCE IN STATE FORMATION: A COMPARATIVE ANALYSIS - Ojo, Emmanuel (Scientia Militaria - South African Journal of Military Studies, 2015)
The basic thrust of this article is an in-depth analysis of the established proposition in the existing literature on civil–military relations (CMR) that the military or instrumentality of force is a sine qua non to the formation and consolidation of the state. From that premise, the article considers the views of the founding fathers of CMR and with historical facts lend credence to that proposition. On the other hand, the article emphasises the fact that force and brute force alone is not sufficient to attain national integration. The study on which this article reports, surveyed stages of state evolution and inferred that force and nation building are in dialectical opposition, whereas consensus and cooperation are required more than force in the process of nationhood. The article infers that in this 21st century, even after attaining nationhood, the state is still in need of very strong armed forces because of the challenges of globalisation, which include terrorism and territorial expansion by neighbouring and far-away states.